Coloring locals : racial formation in Kate Chopin's Youth's companion stories - Shaker, Bonnie James, 1960- (University of Iowa Press, 2003)
Shaker's volume is an important contribution to both Chopin criticism and to the growing field of race research known as whiteness studies. --Choice.